Effects of milk, milk replacer, and milk replacer plus ethoxyquin on the growth performance, weaning stress, and the fecal microbiota of Holstein dairy calves - Wei, Xiaoshi; Zou, Jifu; Zhang, Yiwei; Yang, Jinyong; Wang, Junhong; Wang, Yanming; Wang, Chong (Frontiers in Microbiology, 2023)
The growth and health statuses of calves during the early stages of development have a significant effect on milk production during their first lactation period. Using appropriate milk replacers helps meet the long-term targets of dairy farmers. This study aimed to examine the effects of milk, milk replacer, and milk replacer plus ethoxyquin on growth performance, antioxidant status, immune function, and the gut microbiota of Holstein dairy calves. A total of 36 neonatal dairy calves were randomly divided into three groups and fed different diets: one group was fed milk, another group was fed milk replacer, and the third group was given milk replacer plus ethoxyquin. The supplementation with ethoxyquin was started on day 35 of the feeding period. The calves were weaned on day 45, and the experiment was conducted until day 49. The blood and fecal samples were collected at the end of the animal experiment. The results showed that milk replacers induced poor growth performance (body weight and average daily gain). However, milk replacer plus ethoxyquin aided in growth performance, enhanced the starter intake and blood antioxidative ability, and elevated the concentration of fecal valeric acid. Moreover, fecal fermentation and 16S rRNA analyses showed that milk replacer plus ethoxyquin altered the microbial composition (reducing Alistipes and Ruminococcaceae and increasing Bacteroides and Alloprevotella). Pearson's correlation assays showed that alterations in fecal microbiota strongly correlated with average daily gain and antioxidative ability. The results indicated the potential of milk replacer plus ethoxyquin in modulating the growth of dairy calves and in enhancing their ability to combat stress.